ANALISIS PENGARUH EFISIENSI ASET DAN FINANCIAL LEVERAGE TERHADAP SUSTAINABLE GROWTH RATE DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING - Aida Aqila; Prasetiono Prasetiono (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT In conducting business activities, it is important for companies to measure and pay attention to their Sustainable Growth Rate (SGR) to assess the sustainability of the company, as the basis for planning, and for decision-making by managers. This study aims to analyze the influence of asset efficiency management, measured by Total Asset Turnover (TATO), and financial leverage, measured by short-term debt (STDL) and long-term debt (LTDL), on the Sustainable Growth Rate (SGR) of companies using profitability as a proxy with Return on Asset (RoA) as an intervening variable. The sample used in this study was collected from 24 manufacturing companies in Indonesia listed on the Indonesia Stock Exchange (IDX) with complete data on the research variables during the period 2017-2021. The sample was obtained using purposive sampling with secondary data obtained from the Bloomberg terminal. This study uses multiple linear regression analysis of panel data using IBM SPSS Statistics 25 software. The findings of this study provide an overview that asset efficiency has a significant positive influence on the Sustainable Growth Rate (SGR) both directly and through the intervening variable of Return on Asset (RoA). Meanwhile, only short term debt (STDL) of financial leverage was found to have significant effect on the Sustainable Growth Rate (SGR).